The Draytons and the Davenants - Charles, Elizabeth Rundle, 1828-1896 (Salt Lake City, UT : Project Gutenberg, 2025)
"The Draytons and the Davenants: A Story of the Civil Wars" is a historical novel written in the late 19th century, attributed to the author of "Chronicles of the Schonberg-Cotta Family." The book is set against the backdrop of the English Civil Wars and explores the intersecting lives of two families, the Draytons and the Davenants. Told through the personal recollections and journals of the protagonist, Olive, the narrative blends family history with the larger religious and social struggles of the era. Through its focus on domestic scenes, childhood experiences, and evolving relationships, the novel illuminates the era$1 (Bs conflicts as lived by ordinary people. The opening of the novel is steeped in nostalgia and memory, as Olive, living in New England, reflects on her childhood in England by drawing parallels between her present and her past. The narrative style is intimate, centered on Olive's recollections, including her earliest attempts to record "history" in a childhood journal$1 (Branging from national events like royal ceremonies and persecutions, to personal incidents such as the death of a cow. Early chapters introduce Olive's close-knit family, her philosophical conversations with her brother Roger, the strict but well-meaning Aunt Dorothy, and the gentle Aunt Gretel. The story sets the stage for ongoing familial and ideological conflicts, notably with the arrival and description of the Davenant family and the enchanting Lady Lucy and her daughter Lettice, whom Olive befriends. The opening portion covers themes of innocence, religious strife, moral questioning, and the shaping of allegiances during tumultuous times, providing readers with a deeply personal gateway into the larger historical narrative. (This is an automatically generated summary.)s
Sequel: On both sides of the sea, #75741.
Release date is 2025-03-29
Al Haines
Keywords: Great Britain -- History -- Civil War, 1642-1649 -- Fiction